Covid-19 financial support to small businesses in Switzerland: Evaluation and outlook - Marius Brülhart; Rafael Lalive; Tobias Lehmann; Michael Siegenthaler (ETH Zurich, KOF Swiss Economic Institute, 2020)
What determines small businesses' recourse to public support measures during the Covid-19 crisis? We analyse this question using a survey of 1,011 self-employed workers and small business owners in Switzerland, linked to information pre-dating the crisis. We find that "objective" measures of lockdown affectedness and economic structure explain fairly well how businesses availed of support measures to cover labour costs. Recourse to governmentbacked Corona loans, however, is less well explained by objective characteristics and appears to be driven to a larger degree by behavioural idiosyncrasies across firms. Specifically, previously indebted businesses took out Corona loans more readily than those who had been debt-free before the pandemic. Since Corona uptake is not well in line with firm fundamentals, we propose making loan repayments contingent on future profits. This will more effectively target and sustain businesses that are in trouble today but would be viable in the absence Covid-19. Looking ahead, we also suggest that public support measures should gradually switch from "freezing" the economy towards facilitating structural reallocation. Support to firms whose activity continues to be constrained by the pandemic should be gradually lowered.
hdl:20.500.11850/424045
Keywords: 330; Coronavirus; Wirtschaftskrise; KMU; Subvention; Schweiz